ภูมิทัศน์ประเภทรายการของโทรทัศน์ดาวเทียมในประเทศไทย - นิศรารัตน์ วิไลลักษณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
There are 2 objectives of this research including 1) to study the diversity and the concentration - diffusion of satellite TV’s program channels ; 2) to analyze satellite TV entrepreneurs’ views on these TV channels’ roles and functions.This qualitative research employs 2 studied methods: 1) in-depth interview the executives of satellite entrepreneurs who are members of Satellite Television Association (Thailand) in 2011; 2) review and analysis of studied satellite TV programs and their programming documents.The study about the diversity concentration diffusion of satellite TV’s program channels found that the landscape of these televisions’ genres is drawn as following; 1) the most of satellite TV entrepreneurs come from mass media business background. Most of them are TV entertainment producers and news & current affairs program producers, relatively; 2) there is the wider gap of the viewers’ accessibility to the numbers of TV channels; 3) the imbalance of satellite TV’s program channels’ diversity has still existed because their channels are concentrated on entertainment. According to entrepreneurs’ views on satellite TV’s roles and functions, entertainment is their main role that is consistent with their concentration of entertainment programs.